3D simulation research on the damage of load-bearing structure of prefabricated building based on BIM model. (30th July 2021) - Guo, Ximei; Lu, Huawu
In order to overcome the problems of low detection accuracy and poor detection performance existing in the traditional method of building load-bearing structure damage simulation, this paper proposes a new three-dimensional simulation detection system of building load-bearing structure damage based on BIM model. The system obtains the data of the load-bearing structure of the prefabricated building through the relevant monitoring equipment and 3D laser scanner. The data processing layer constructs the safety rule base, realises the data format transformation, noise filtering and transmission to the application layer. The application layer realises the damage detection of the load-bearing structure of the prefabricated building through the structure damage detection method based on 3D laser scanning and BIM. The experimental results show that compared with the traditional damage detection system, the system has a higher accuracy of damage detection, which can detect only 0.02 mm long damage in the load-bearing structure of prefabricated buildings.